1999
DOI: 10.1007/s005350050296
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori -negative gastric and duodenal ulcers

Abstract: It is unclear whether Helicobacter pylori infection is essential to the development of peptic ulcers. In this study, we examined the rates of H. pylori-negativity among patients with peptic ulcers. We also attempted to clarify the characteristics of H. pylori-negative peptic ulcers to throw light on the pathogenesis of peptic ulcers. The study included 215 consecutive patients with gastric ulcers (GUs) and 120 consecutive patients with duodenal ulcers (DUs). After routine endoscopic examination and phenol red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 12 publications
2
19
1
1
Order By: Relevance
“…Peptic ulcer disease is still highly associated with H. pylori infection (95.7% DU, 87% benign GU); only 1.6% of DU and 4.1% of GU were not associated with either H. pylori infection or NSAID use, as reported in Spain [16]. Similar results have been reported earlier for the Japanese patients; the investigators, in an attempt to clarify the characteristics of H. pylori-negative peptic ulcers, found very few differences between H. pylori-negative and H. pylori-positive peptic ulcers [17]. Xia et al [18] reported that GU associated with H. pylori infection and/or NSAID use occurred mostly in older people, whereas non-H. pylori, non-NSAID GU were more common in younger patients.…”
Section: Discussionsupporting
confidence: 83%
“…Peptic ulcer disease is still highly associated with H. pylori infection (95.7% DU, 87% benign GU); only 1.6% of DU and 4.1% of GU were not associated with either H. pylori infection or NSAID use, as reported in Spain [16]. Similar results have been reported earlier for the Japanese patients; the investigators, in an attempt to clarify the characteristics of H. pylori-negative peptic ulcers, found very few differences between H. pylori-negative and H. pylori-positive peptic ulcers [17]. Xia et al [18] reported that GU associated with H. pylori infection and/or NSAID use occurred mostly in older people, whereas non-H. pylori, non-NSAID GU were more common in younger patients.…”
Section: Discussionsupporting
confidence: 83%
“…Compared with our results ten years ago, there has been a significant change in the prevalence of H. The prevalence of H. pylori infection in GU and DU showed increasing and decreasing trends, respectively, compared with our results from ten years ago. It has been shown in several studies that DU is more commonly related to H. pylori infection than GU [4][5][6]. Widespread eradication of H. pylori might have a more profound effect on the prevalence of DU than GU.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection has been found in 73-100% of patients with duodenal ulcers (DU) and 65-100% of patients with gastric ulcers (GU) [2][3][4][5][6][7]. Because H. pylori infection is generally regarded as a causal factor in the pathogenesis of PUD, it has been widely eradicated in Korea, similar to other countries.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] However, some ulcers are apparently unrelated to those risk factors, and there is considerable variation in the reported proportion of such ulcers. Recent reports from North America suggest that up to 50% of ulcers are H pylori negative, [6][7][8] whereas in other parts of the world, a proportion of H pylori-negative ulcers remains much lower at less than 5%.…”
mentioning
confidence: 99%